AKTIVITAS ANTIOKSIDAN DAN POTENSI TABIR SURYA PADA ECO-ENZIM - Nur Yaqin; Santi Agustin Dwi Widya (Jurnal Penelitian Multidisiplin, 2024)
Sunscreen is a material used to protect the skin from exposure to ultraviolet (UV) rays. Its effectiveness in reflecting or absorbing UV rays can be determined by the Sun Protecting Factor (SPF) value. The effectiveness of eco-enzymes can be seen from the antioxidant value of the SPF value, where this antioxidant is determined by the DPPH method. Abundant antioxidant components are found in plants, especially fruit peels. Fruit skin waste, which is generally just thrown away, can actually be put to good use. Eco- enzyme is fermented mixture of organic kitchen waste in the form of fruit and vegetable scraps with the addition of brown sugar and water. Eco-Enzim Liquid contains various ingredients including alcohol, enzymes, organic acids and metabolite compounds. The purpose of this study was to determine the value of antioxidant activity and sunscreen potency on Eco-Enzim which can be seen from the SPF value. This research was conducted using the UV-Vis spectrophotometry method. From this test, the results obtained that Eco- Enzyme contains secondary metabolites of alkaloids, tannins, flavonoids and saponins. And obtained the value of antioxidant activity (IC₅₀) of 143.753 which indicates moderate antioxidant. In determining the SPF value, the SPF value was obtained at concentrations (15,25,50,75,100) ppm, respectively 0.609; 1.153; 1,933; 3,757; 6,363. Concentrations of 15 and 25 ppm include the minimum category. The concentration of 75 ppm is included in the moderate category and the concentration of 100 is included in the extra category.